2020
DOI: 10.1136/bmjopen-2019-035823
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the high burden of hypertension and its predictors among adult population in Hosanna town, southern Ethiopia: a community-based cross-sectional study

Abstract: ObjectiveHypertension is a global public health problem, with its burden increasing particularly in developing countries. However, it has not yet received due attention in Ethiopia. The aim of this study was to determine the prevalence and associated factors of hypertension among adult population in Hosanna town, southern Ethiopia.DesignCommunity-based cross-sectional study.SettingHosanna town, southern Ethiopia.ParticipantsAdult population aged ≥18 years (n=634) were recruited by a multistage stratified sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…This finding is consistent with a study done in eastern Ethiopia, Harar jugal hospital which revealed that increased glucose levels in the blood were significantly associated with the magnitude of hypertension and northeast Ethiopia [2,3]. This finding is also supported by a previous study done on the burden of hypertension among adult persons which demonstrated that diabetic mellitus was a strong correlates of hypertension [12]. The other justification could be the shared risk factors like obesity and physical inactivity may contribute to hypertension risks.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with a study done in eastern Ethiopia, Harar jugal hospital which revealed that increased glucose levels in the blood were significantly associated with the magnitude of hypertension and northeast Ethiopia [2,3]. This finding is also supported by a previous study done on the burden of hypertension among adult persons which demonstrated that diabetic mellitus was a strong correlates of hypertension [12]. The other justification could be the shared risk factors like obesity and physical inactivity may contribute to hypertension risks.…”
Section: Discussionsupporting
confidence: 91%
“…The optimal level of LDL was less than 100 mg/dl and greater than 100 mg/dl was defined as high. HDL is considered as desirable if it is > 40 mg/dl for men and > 50 mg/dl for women [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed increasing age and being male as important predictors of hypertension. Supporting evidence was reported from the studies conducted in Ethiopia and elsewhere ( Asemu et al, 2021 , Dereje et al, 2020 , Hasan et al, 2018 , Kumma et al, 2021 , Omar et al, 2020 , Tiruneh et al, 2020 , Zaki et al, 2021 ). Hypertension increases with age due to structural changes in the walls of blood vessels ( Pinto, 2007 ), and men are more likely to be susceptible to behavioral risk factors.…”
Section: Discussionsupporting
confidence: 70%
“…7 A nationwide NCD risk factor survey in 2015 reported that the prevalence of hypertension was 15.7% in men and 16.5% in women, 9 10 and a recent survey conducted in southern Ethiopia reported 19.3% in men and 14.2% in women as well. 11 Prevention and control of hypertension are urgently required in countries such as Ethiopia, of which healthcare systems are yet insufficient to manage cardiac diseases and stroke, or serious consequences of hypertension. 12 Strengths and limitations of this study ► This is the first study to investigate the difference of anthropometric indices of obesity in association with hypertension in northern Ethiopia separately for sex.…”
Section: Introductionmentioning
confidence: 99%